Anthropometric Measurements to Predict NICU Admission for Infants of Diabetic Mothers (Bangladesh Journal of Medical Science, 2022)
Aim: Can NICU admission of IDM be predicted by anthropometric measurements like birth weight, lenght, head circumference (HC), mid upper arm circumference (MUAC) or triceps skin fold thickness (TSFT).Method: Eighty-six-term IDMs were analyzed prospectively. MUAC, HC and TSFT were measured within 48 hours of life. Prenatal-natal-postnatal problems; NICU admission; maternal characteristics, HbA1c were recorded.Results: Mean birth weight, gestational age were 3453.3±582.4g and 38.0±0.97weeks. 63.9% of IDMs was admitted to NICU. 56.3% hospitalized due respiratory problems; 32,7 % required endotracheal intubation. Mean MUAC, TSFT, HC and MUAC/HC ratio were 11.2±1.1 cm, 7.1±2.2 mm, 35.0±1.8 cm and 0.32±0.03 cm respectively for all. Although there was no significant relation between NICU admission and MUAC (p=0.071), TSFT and MUAC/HC were significantly higher in babies admitted to NICU (p=0.006 for TSFT, p